The Empty Ballot Movement as a Form of Protest Voting in the 2024 Brebes Regency Regional Election - Hermanto, Bambang; Khu, Stanley; Adi Pamungkas, Wahyu; Setiyawan, Wahyu Beny Mukti; Rakhmanto, Bambang (Journal Politique, 2026)
The phenomenon of the empty ballot in the 2024 Regional Head Election (Pilkada) of Brebes Regency attracted significant public attention after receiving 341,407 votes (40.4%), while voter turnout reached only 58.27%, the lowest participation rate in Central Java. This study aims to describe the Empty Ballot Movement as a form of protest voting by employing a qualitative method involving 15 informants, consisting of the movement's leader, community leaders, volunteers, and residents. The findings reveal that the movement emerged as a response to dissatisfaction with local democracy, driven by three main factors: the dominance of oligarchic politics that produced a single-candidate election through the consolidation of political party support; the perception that the sole candidate represented a political dynasty due to connections with former officials previously implicated in corruption cases; and the proposed IDR 13,000 shallot price policy, which was perceived as harmful to farmers. The Empty Ballot Movement successfully garnered public sympathy and became a symbol of protest voting against political practices regarded as undemocratic.